Chien-Shiung Wu pioneering physicist and atomic researcher - Cooperman, Stephanie (New York Rosen Pub. Group, 2004)
Explores the work of Chien-Shiun Wu, a physicist and atomic researcher, and examines the hardships she endured to reach the top of her field
Planting the seeds in China -- Putting down roots in America -- Growing with the war effort -- Springtime for Wu -- Pollinating the world -- A mind in full bloom
Includes bibliographical references (p. [106]-108) and index
1
Keywords: Wu, C. S -- 1912-1997 -- Juvenile literature; Wu, C. S -- 1912-1997; Physicists -- United States -- Biography -- Juvenile literature; Physicists; Women -- Biography